Theoretical-critical discourse on fantasy literature of the late 20th century - Mesarova, Eva (Romanica Olomucensia, 2014)
For many 20th-century writers, fantasy was a way to demonstrate the power of literature to create worlds different from the known, but nonetheless originating from reality. This article aims to attract attention to the main attitudes espoused in the literary theory and criticism of late-20th-century Italy. Some of the critics followed in the footsteps of Todorov and suggested corrections to his typology. Others, however, rejected Todorov's schematic representation and suggested a typology based on a broader contrast between the fantastic and the realistic. Finally, there were attempts to use the analysis of Todorov's taxonomies as a springboard for innovative solutions. In the last thirty years of the 20th century, fiction was considered a ``mode'' which employs elements similar to postmodern poetics.
Keywords: Italian literature; the fantastic and the realistic; paradigm of reality.